Diagnostic tools for female urethral diverticulum: Current perspectives - Gloria Calagna; Marco Vella; Maria Elena Mugavero; Giorgio Gugliotta; Salvatore Polito; Antonino Perino; Gaspare Cucinella (Urogynaecologia International Journal, 2019)
Although once considered quite a rare condition in the past, female urethral diverticulum (UD) would now appear to have a higher frequency, perhaps due to greater attention from physicians. To date, there is no agreement on which is the best method for diagnosis of female UD. Traditionally, the approach was based on quite invasive techniques, such as voiding cystourethrography, and double-balloon urethrography, with satisfactory results but relevant limitations. More recent high-resolution imaging techniques, such as 2D-3D ultrasonography (US) and magnetic resonance imaging (MRI) have also been applied in the study of the abnormalities of the female urethra. US had the advantage of the outpatient setting, non-invasiveness and absence of contrast medium use; MRI, is characterized by high sensitivity thanks to multiplanar capability, with an optimal characterization of periurethral diseases or its abnormalities, and lack of ionizing radiation. A real innovation is represented by computer tomography-voiding cystourethrography, a rapid technique that allows for high quality simultaneous 2D and 3D images of the urethra, well correlated to MRI and consequently with surgical results. Here, we report and comment the available tools in the diagnosis of female UD, focusing particularly on pros and contra of different methods.